Un radical discret : l’esclavage dans la pensée singulière de Félix Tanco Bosmeniel - Karim Ghorbal (Mélanges de la Casa de Velázquez)
This article is intended as an approximation to the life and the thought of Félix Tanco Bosmeniel (1796-1871), considered here as a «basket case». His unequivocal condemnation of slavery made him a marginal player, whose peculiar career highlights the possibilities and the barriers in Cuban society. The ideological radicality of his actions and writings invites a reconsideration of pre-conceived notions, leaving aside the specifics of his discourse, which allows us to break away from a certain teleological way of viewing the colonial history of Cuba. An examination of his thought on the subject of slavery likewise provides an opportunity to question the ethical value of the sometimes ambiguous notion of «abolitionism». The silences of historians in relation to Tanco, the promoter of an integrationist discourse that was «ahead of its time», in a sense reflect the racist realities which have determined the way in which slavery is represented.